ATR-CHK1 pathway as a therapeutic target for acute and chronic leukemias. (August 2020) - Boudny, Miroslav; Trbusek, Martin
Highlights: ATR-CHK1 pathway is a promising therapeutic target for leukemia treatment. ATR and CHK1 inhibition showed great results in preclinical testing in leukemias. Results of clinical trials of DDR inhibitors in leukemias are so far insufficient. Abstract: Progress in cancer therapy changed the outcome of many patients and moved therapy from chemotherapy agents to targeted drugs. Targeted drugs already changed the clinical practice in treatment of leukemias, such as imatinib (BCR/ABL inhibitor) in chronic myeloid leukemia (CML) and acute lymphoblastic leukemia (ALL), ibrutinib (Bruton's tyrosine kinase inhibitor) in chronic lymphocytic leukemia (CLL), venetoclax (BCL2 inhibitor) in CLL and acute myeloid leukemia (AML) or midostaurin (FLT3 inhibitor) in AML. In this review, we focused on DNA damage response (DDR) inhibition, specifically on inhibition of ATR-CHK1 pathway. Cancer cells harbor often defects in different DDR pathways, which render them vulnerable to DDR inhibition. Some DDR inhibitors showed interesting single-agent activity even in the absence of cytotoxic drug especially in cancers with underlying defects in DDR or DNA replication. Almost no mutations were found in ATR and CHEK1 genes in leukemia patients. Together with the fact that ATR-CHK1 pathway is essential for cell development and survival of leukemia cells, it represents a promising therapeutic target for treatment of leukemia. ATR-CHK1 inhibition showed excellent results in preclinical testing in acute and chronic leukemias. However, results in clinical trials are so far insufficient. Therefore, the ongoing and future clinical trials will decide on the success of ATR/CHK1 inhibitors in clinical practice of leukemia treatment.